Avoiding costly downtime – how MSPs can manage their networks. Issue 2 (February 2021) - Walsh, Brendan
Abstract : For managed service providers (MSPs), managing a network is a big responsibility. Availability is the top priority in order to provide customers with constant access to critical applications that help to ensure that their businesses are able to function. 1 When a network goes down this can be due to a variety of causes such as cyber attack, hardware failure or human error and this downtime can be extremely costly. ITIC's latest 'Global Server Hardware, Server OS Reliability Survey' found that a single hour of downtime now costs 98% of firms at least $100, 000. 2 For managed service providers (MSPs), managing a network is a big responsibility. When it goes down – perhaps as the result of a cyber attack – the results can be costly. The need for network resilience has become even greater during the pandemic. The requirement to work from home has placed increased strain on networks and greater importance on seamless connectivity. The need for MSPs to ensure greater resilience and uptime may be here to stay, says Brendan Walsh of Opengear.